Inhibitory effect of thiourea derivatives on the growth of blue-green algae. (15th September 2021) - Kasan, Nor Azman; Yusof, Siti Zafirah Mohamad; Manan, Hidayah; Khairul, Wan Mohd; Zakeri, Hazlina Ahamad
Abstract: High nutrient loading in aquatic environment has become the main causative of harmful algae blooms (HABs) in water resources particularly pond, lake and river. HABs are mostly dominated by microalgae derived from the group of blue-green algae which are capable of releasing harmful toxins. Therefore, this study aims to investigate the inhibitory effects of thiourea derivatives on the growth of such blue-green algae. Thiourea derivatives have been proven to exhibit antifungal and antibacterial effects. However, there is still limited study had been conducted on the effect of thiourea derivatives toward blue-green algae species in recent years. In this research, a species of blue-green algae from Kenyir Lake, Terengganu, Malaysia was successfully isolated using morphological characters and molecularly identified as Synechoccus elongatus . Four new thiourea derivative compounds were also successfully synthesised. The compounds were designed with variation on different R-substitution group and characterised using Nuclear Magnetic Resonance (NMR) to confirm their molecular structure. Those compounds were characterised as 1-Benzyl-3-(3, 5-dimethoxy-benzoyl)-thiourea (C1), 1-(3-Chloro-benzyl)-3-(3, 5-dimethoxy-benzoyl)-thiourea (C2), 1-(3, 5-Dimethoxy-benzoyl)-3-(3-methyl-benzyl)-thiourea (C3) and 1-(3, 5-Dimethoxy-benzoyl)-3-(3-trifluoromethyl-benzyl)-thiourea (C4). For the inhibition assessment, S. elongatus were treated with C1–C4 for 5 day at concentration of 2, 5, 10 and 20 μg/ml, respectively. C3 compound showed the highest inhibition percentage with 98% of inhibition after 5 days treatment. By using Bradford method, protein extraction of S. elongatus was conducted at the highest inhibition percentage. Protein concentration of treated species was observed with 3.28 μg/ml as compared to protein concentration of control with 6.48 μg/ml. This result indicated the reduction of protein content after the treatment. Protein band pattern was identified intensed after the treatment SDS PAGE was carried out. The thiourea derivatives compound proved to have successfully inhibited the growth of blue-green algae. Hence, further study should be carried out to ensure the compound can be practically utilized in the pond and in natural environment. Highlights: 4 new thiourea derivatives were synthesised:1-Benzyl-3-(3, 5-dimethoxy-benzoyl)-thiourea (C1), 1-(3-Chloro-benzyl)-3-(3, 5-dimethoxy-benzoyl)-thiourea (C2), 1-(3, 5-Dimethoxy-benzoyl)-3-(3-methyl-benzyl)-thiourea (C3) and 1-(3, 5-Dimethoxy-benzoyl)-3-(3-trifluoromethyl-benzyl)-thiourea (C4) . C3 compound showed the highest inhibition percentage with 98% of inhibition after 5 days treatment. The number of S. elongatus cells measured was a significant decreased for 2, 5, 10 and 20 μg/ml concentration in all of C1– C4 thioureas derivatives as compared to control. Thiourea derivatives successfully inhibit the growth of blue-green algae of Synechoccus elongatus.